2017 IEEE Vehicle Power and Propulsion Conference (VPPC) 2017
DOI: 10.1109/vppc.2017.8330874
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Analysis of Fin Cooling Large Format Automotive Lithium-Ion Pouch Cells

Abstract: The version presented here may differ from the published version or, version of record, if you wish to cite this item you are advised to consult the publisher's version. Please see the 'permanent WRAP URL' above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…This can be more crucial in case of large format batteries with high current flows which generate a higher amount of heat and have a larger surface area. Generally it is difficult to manage the heat from large format batteries very efficiently [18][19][20][21]. This part presents the impact of nonidentical initial temperatures on the performance of the parallel cells within the (1S 5P) ESS during the constant 3C discharge event.…”
Section: Resultsmentioning
confidence: 99%
“…This can be more crucial in case of large format batteries with high current flows which generate a higher amount of heat and have a larger surface area. Generally it is difficult to manage the heat from large format batteries very efficiently [18][19][20][21]. This part presents the impact of nonidentical initial temperatures on the performance of the parallel cells within the (1S 5P) ESS during the constant 3C discharge event.…”
Section: Resultsmentioning
confidence: 99%
“…It enhances the cooling efficiency while still maintaining decent thermo‐physical properties. On the other hand, oils, such as mineral or synthetic oils, are employed as alternative coolants 37,38 . They have lower heat capacity compared to water and ethylene glycol, but they exhibit higher resistance to flow and thermal stability, making them suitable for specific applications 39,40 .…”
Section: Liquid Cooled Thermal Management Systemmentioning
confidence: 99%
“…On the other hand, oils, such as mineral or synthetic oils, are employed as alternative coolants. 37,38 They have lower heat capacity compared to water and ethylene glycol, but they exhibit higher resistance to flow and thermal stability, making them suitable for specific applications. 39,40 The choice of coolant can significantly impact the battery's overall thermal performance, affecting its ability to dissipate heat efficiently and maintain optimal operating temperatures.…”
Section: Liquid Cooled Thermal Management Systemmentioning
confidence: 99%
“…1f. Given the good contact between the cooling fins and the cell surface, the thermocouple measurements are used as pseudo-cell surface measurements [22]. Each cell is individually connected to cell cycling channels, which can provide a maximum current of 400 A per cell.…”
Section: Experimental Rigmentioning
confidence: 99%
“…Specifically, for cylindrical cells [19], internal cooling with an inserted heat pipe system and/or double tab cooling strategies were required to limit the maximum cell temperature gradient to 5℃, where conventional radial surface cooling gave rise to temperature gradients exceeding 15 ℃. Other experimental studies for pouch cells [22] have also demonstrated the need for more advanced cooling materials to avoid the evolution of thermal gradients exceeding 10 ℃ when exposed to the HP-C. Hosseinzadeh et al [23] developed a 1D electrochemical-thermal model to simulate the heat generation a 53 Ah pouch cell at various ambient temperatures. In their study a cell was subject to the HP-C, and a profile derived from the WLTP (Worldwide Harmonised Light Vehicle Test Procedure) Class 3 to validate the model and predict the increase in cell temperature arising from these vastly different automotive use cases.…”
Section: Introductionmentioning
confidence: 99%